Investigation of the antibiofilm capacity of peptide-modified stainless steel. Issue 3 (7th March 2018) - Cao, Pan; Li, Wen-Wu; Morris, Andrew R.; Horrocks, Paul D.; Yuan, Cheng-Qing; Yang, Ying
Abstract : Biofilm formation on surfaces is an important research topic in ship tribology and medical implants. In this study, dopamine and two types of synthetic peptides were designed and attached to 304 stainless steel surfaces, aiming to inhibit the formation of biofilms. A combinatory surface modification procedure was applied in which dopamine was used as a coupling agent, allowing a strong binding ability with the two peptides. X-ray photoelectron spectroscopy (XPS), elemental analysis, contact angle measurement and surface roughness test were used to evaluate the efficiency of the peptide modification. An antibiofilm assay against Staphylococcus aureus was conducted to validate the antibiofilm capacity of the peptide-modified stainless steel samples. XPS analysis confirmed that the optimal dopamine concentration was 40 µg ml −1 in the coupling reaction. Element analysis showed that dopamine and the peptides had bound to the steel surfaces. The robustness assay of the modified surface demonstrated that most peptide molecules had bound on the surface of the stainless steel firmly. The contact angle of the modified surfaces was significantly changed. Modified steel samples exhibited improved antibiofilm properties in comparison to untreated and dopamine-only counterpart, with the peptide 1 modification displaying the best antibiofilm effect. The modified surfaces showed antibacterial capacity. The antibiofilm capacity of the modified surfaces was also surface topography sensitive. The steel sample surfaces polished with 600# sandpaper exhibited stronger antibiofilm capacity than those polished with other types of sandpapers after peptide modification. These findings present valuable information for future antifouling material research.